The Effect of Pulsatile and Non-Pulsatile Extra Corporeal Perfusion on Cerebral Oxygen Saturation in Cardiopulmonary Bypass Patients (Flow Type On Cerebral Oxygenatıon) - Ayhan ŞAHİN; İlker YILDIRIM; Onur BARAN; Mustafa GÜNKAYA; Cavidan ARAR; Ercan GÜNERİ (Namık Kemal Tıp Dergisi, 2019)

(untitled)
Aim:The flow type generated by a heart-lung machine is important in cardiopulmonary bypass. The use of pulsatile flow versus non-pulsatile flow during cardiopulmonary bypass has been a controversy among clinicians. We compared the effect of non-pulsatile and pulsatile flow during cardiopulmonary bypass on cerebral oxygenation.Materials and Methods:We conducted a retrospective study of 50 adult patients who underwent coronary artery bypass graft surgery at our university hospital, with near infrared spectroscopy used to compare differences in cerebral oxygenation between the pulsatile and non-pulsatile flow type.Results:There was no difference between the effect of pulsatile and non-pulsatile flow on the saturation of hemoglobin (SpO2), nor on the partial pressure of oxygen (pO2) and carbon dioxide (pCO2). The near infrared spectroscopy results were not different between the two flow types.Conclusion:There was no effect of the flow type generated by a heart-lung machine (pulsatile or non-pulsatile) on cerebral oxygenation in adult patients.